Research on Consumer Willingness to Purchase Time-honored Brand Products Based on TPB Theory in the New Media Environment - Zhang, Qiongqiong (International Journal of Global Economics and Management, 2024)
In the context of the digital economy, utilizing new media for marketing and brand promotion has become the direction of digital transformation for China’s time-honored brand enterprises. This paper takes consumer research data as a sample and based on the theory of planned behavior (TPB), establishes a mechanism model for the impact of consumer willingness to purchase China’s time-honored brand products in the new media environment. The conclusion of this paper is as follows: First, subjective norms become the most important factor influencing consumer attitudes. Secondly, the level of new media marketing for time-honored brands can significantly influence consumer attitudes and promote the conversion of consumer purchase intention. Finally, perceived behavioral control can significantly influence the attitude of consumers, but it cannot significantly affect their behavior. This paper provides policy recommendations for improving the competitiveness and marketing level of China’s time-honored brands in the new media environment from the aspects of social media construction, new media operation, promoting product innovation and model innovation.